The relationship between work-life balance and job satisfaction among the support staff in Agriculture Department, Kota Samarahan / Nur Syazwanie Ismail - Ismail, Nur Syazwanie (2018)
The core purpose of this study is to investigate the relationship between Work-Life Balance and Job Satisfaction in Agriculture Department, Kota Samarahan. The data is collected keeping in consideration of demographic factors and factors affect for job satisfaction. Factors involved are job satisfaction and work-life balance with the respect to Working Hours (r=.050, p<0.05), Working Conditions (r=.260*, p<0.05), and Work Pressure (r=.064, p<0.05). The data for the present study was collected through questionnaires. A total of 90 questionnaires were distributed among support staff in Agriculture Department, Kota Samarahan which 87 were returned back after filling. The data then analyzed using SPSS version 20, tests applied is correlation. The findings suggest that work-life balance has an insignificant impact on employee job satisfaction in Agriculture Department, Kota Samarahan. It can be concluded that work life balance did not have much impact on employee job satisfaction. This research can be beneficial for organization and future researchers to improve the understanding about work-life balance and job satisfaction. Top management should realize the importance of work-life balance and its adverse effect on job satisfaction. It is suggested that consideration be given to the development of guidelines in order to ensure that working conditions should not effects the work-life balance of employees. Then, future researchers can use different methods of instrument such as interview, observation, or personality test in order to obtain better result.